LA FORMACIÓN PERMANENTE EN ATENCIÓN A LA DIVERSIDAD DESDE UN PROYECTO EDUCATIVO DE CENTRO - Venet Muñoz, Regina (2009)
http://www.scielo.org.bo/scielo.php?pid=S1997-40432009000200009&script=sci_arttext&tlng=en